Bone resorption: an actor of dental and periodontal development? - Gama, Andrea; Navet, Benjamin; Vargas, Jorge William; Castaneda, Beatriz; Lézot, Frédéric (Frontiers in Physiology, 2015)
Dental and periodontal tissue development is a complex process involving various cell-types. A finely orchestrated network of communications between these cells is implicated. During early development, communications between cells from the oral epithelium and the underlying mesenchyme govern the dental morphogenesis with successive bud, cap and bell stages. Later, interactions between epithelial and mesenchymal cells occur during dental root elongation. Root elongation and tooth eruption require resorption of surrounding alveolar bone to occur. For years, it was postulated that signaling molecules secreted by dental and periodontal cells control bone resorbing osteoclast precursor recruitment and differentiation. Reverse signaling originating from bone cells (osteoclasts and osteoblasts) toward dental cells was not suspected. Dental defects reported in osteopetrosis were associated with mechanical stress secondary to defective bone resorption. In the last decade, consequences of bone resorption over-activation on dental and periodontal tissue formation have been analyzed with transgenic animals (RankTg and Opg-/- mice). Results suggest the existence of signals originating from osteoclasts toward dental and periodontal cells. Meanwhile, experiments consisting in transitory inhibition of bone resorption during root elongation, achieved with bone resorption inhibitors having different mechanisms of action (bisphosphonates and RANKL blocking antibodies), have evidenced dental and periodontal defects that support the presence of signals originating bone cells toward dental cells. The aim of the present manuscript is to present the data we have collected in the last years that support the hypothesis of a role of bone resorption in dental and periodontal development.